2002
DOI: 10.1136/bjo.86.10.1076
|View full text |Cite
|
Sign up to set email alerts
|

Ocular disease in patients with tuberculosis and HIV presenting with fever in Africa

Abstract: Aims: To investigate ocular disease in patients with tuberculosis (TB) and HIV in Africa presenting with fever, and to determine if indirect ophthalmoscopy is useful in the diagnosis of mycobacteraemia. Methods: A prospective study of all adult patients admitted with fever to a large central hospital in Malawi, Africa. All recruited patients had an ophthalmic examination, HIV tests, chest x ray, sputum examinations, bacterial and mycobacterial blood cultures, and malaria slide to observe the presence of parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…[15][16][17][18][19] The presentation of granulomatous inflammation in HIV/AIDS patients in study are in accordance to several other studies which were mainly choroidal granulomas and tubercles. [20][21][22][23][24][25][26][27] Our findings that ocular TB in HIV/ AIDS patients all have systemic manifestation are in accordance to Babu et al study that found in HIV/ AIDS patients, all ocular TB patients have pulmonary TB, and among them two cases have coexistent central nervous system TB and one case had abdominal TB. In that study also found that the CD4+ cell counts ranged from 14 to 560 cells/µL with mean 160.85 cells/µL.…”
Section: Discussionsupporting
confidence: 80%
“…[15][16][17][18][19] The presentation of granulomatous inflammation in HIV/AIDS patients in study are in accordance to several other studies which were mainly choroidal granulomas and tubercles. [20][21][22][23][24][25][26][27] Our findings that ocular TB in HIV/ AIDS patients all have systemic manifestation are in accordance to Babu et al study that found in HIV/ AIDS patients, all ocular TB patients have pulmonary TB, and among them two cases have coexistent central nervous system TB and one case had abdominal TB. In that study also found that the CD4+ cell counts ranged from 14 to 560 cells/µL with mean 160.85 cells/µL.…”
Section: Discussionsupporting
confidence: 80%
“…AIDS patients in developing countries. 13,14 Variation in the manifestation of ocular AIDS in developed and developing countries is presumed to be due to the early and high mortality rate in people living with HIV-AIDS in developing countries. This is coupled with differences in HIV subtype, race, as well as the influence of co-morbid diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Most informed respondents had been enlightened by health workers (20, 55.6%). Few respondents (16,14.3%) had HIV-AIDS ocular manifestations. Squamous cell carcinoma was the most common ocular manifestation.…”
Section: Methodmentioning
confidence: 99%
“…Published work is uneven and inconsistent, particularly with regard to Africa, 31,32,34,38,39 for reasons that remain unclear. Studies are diffi cult to compare because of diff erences in design, patient population, and reporting of HIV status.…”
Section: Personal Viewmentioning
confidence: 99%
“…Two studies 34,35 specifi cally address choroidal tuberculosis in patients later discovered to have bacteraemia because of Mycobacterium tuberculosis: lesions were identifi ed in three (5·7%) of 53 consecutive patients admitted to a hospital in Malawi because of fever 34 and in fi ve (50%) of ten patients who were in an intensive care unit in a hospital in India. 35 Mycobacteraemia was fi rst reported in patients with AIDS in 1986, 55 and is associated with low CD4 counts, disseminated infection, severe disease, and high mortality, 56 including a report from Tanzania of 50% mortality in 36 days.…”
Section: Personal Viewmentioning
confidence: 99%